Structural features and hydro-mechanical behaviour of a compacted andesitic volcanic soil. Issue 3 (9th July 2018) - Hernandez, O.; Cordão Neto, M. P.; Caicedo, B.
Abstract : Soils derived from volcanic ash occupy 0.84% of the soils worldwide and this proportion increases in countries located on the Andean mountains. Those soils have very unusual properties due to the presence of clay minerals not found in sedimentary soils. Particularly, the hydromechanical and structural properties of volcanic soils undergo huge changes depending on the degree of pre-drying of the samples. Although the main characteristics of volcanic soils have been studied during the last fifty years, few works focused on the hydromechanical and structural behaviour of compacted volcanic soils, which is the purpose of this study. The behaviour of the volcanic soil was evaluated using mineralogical characterisation tests, thermogravimetric analysis, compressibility, direct shear, water retention curves and distribution of pores in the structure. The results showed the high irreversibility of the characteristics of the soil depending on the changes in water content that the soil undergoes before compaction.